Unemployment, Excess Capacity, and Benefit-Cost Investment Criteria: Some Supplementary Estimates - Haveman, Robert; Krutilla, John (The Review of Economics and Statistics, 1967)
Robert Haveman, John Krutilla, Unemployment, Excess Capacity, and Benefit-Cost Investment Criteria: Some Supplementary Estimates, The Review of Economics and Statistics, Vol. 49, No. 4 (Nov., 1967), pp. 654-655